2018
DOI: 10.1002/jgm.3053
|View full text |Cite
|
Sign up to set email alerts
|

Arg399Gln substitution in XRCC1 as a prognostic and predictive biomarker for prostate cancer: Evidence from 8662 subjects and a structural analysis

Abstract: Based on these results, the XRCC1-Arg399Gln polymorphism might be a risk factor for PCa and it could be considered as a prognostic and predictive biomarker for susceptible men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…It is suggested that the role of these three mechanisms in male infertility must be further explored in future studies. Some recent reports have investigated the effects of genetic polymorphisms on molecular aspects of protein and RNA by in silico tools (Karimian et al, 2018[ 26 ]; Nejati et al, 2018[ 41 ]; Zamani-Badi et al, 2018[ 65 ]; Noureddini et al, 2018[ 44 ]).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the role of these three mechanisms in male infertility must be further explored in future studies. Some recent reports have investigated the effects of genetic polymorphisms on molecular aspects of protein and RNA by in silico tools (Karimian et al, 2018[ 26 ]; Nejati et al, 2018[ 41 ]; Zamani-Badi et al, 2018[ 65 ]; Noureddini et al, 2018[ 44 ]).…”
Section: Discussionmentioning
confidence: 99%
“…There are several reported polymorphisms in ABCA1 gene such a R230C, R1587K, and V825I which one of them is R219K polymorphism. Measurement of the molecular effect of polymorphisms by bioinformatics software could be an appropriate tool for evaluation of the effects of SNPs on structure and function of the interested protein 56‐60 . In the current project, we have evaluated the impacts of p.R219K polymorphisms on the protein structure of ABCA1.…”
Section: Discussionmentioning
confidence: 99%
“…The SNPs on the promoter of a gene may alter the gene expression however the SNPs in the intron regions could alter the production of mature mRNA by interfering with the splicing process (Mobasseri et al, 2019;Zamani-Badi et al, 2019). But, the missense mutations could alter the structure and function of proteins (Noureddini et al, 2018;Bafrani et al, 2019) what may be true for GSTP1-Ile105Val genetic variation. Evaluation of the impacts of genetic variations by biological experiments is a very difficult process and evaluation of these impacts could be much easier with the in silico tools (Tameh et al, 2018;Zamani-Badi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%